IMPLEMENTASI CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PUBLIK YANG MASUK DALAM PEMERINGKATAN CORPORATE GOVERNANCE PERCEPTION INDEX (CGPI) TAHUN 2008-2010 - Herry Sunarto (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2012)
During 1998, not only monetary crisis happened but also politics crisis suddenlybecame a trend in Indonesia. Many cases of corruption in our country havecauses many industries lost their investor’s trust. Theoretically, good corporategovernance practice can enhance company’s value by increasing theirperformance and generally corporate governance can increase the investor’strust. But in reality, one of the causes of monetary crisis was how weak thecorporate governance was. This research is to find out whether corporategovernance affects the company’s performance. Based on the analyzed and test,at statistic á (5%), there is significant effect between the implementation of the corporate governance and the operational performance of the company which proxy by Return on Equity (ROE) and Net Profit Margin (NPM). But have no significant effect between the implementation of the corporate governance and the operational performance of the company which proxy by Return on Asset (ROA).